2000
DOI: 10.1143/jjap.39.5645
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Dielectric Properties of Bi-Added Ba4Nd9+1/3Ti18O54 Solid Solutions

Abstract: We have investigated the formation and microwave dielectric properties of the tungstenbronze-type like solid solutions, that is, Bi ions dissolved in Ba6-3x Nd8+2x Ti18O54 solid solution with x=2/3. According to the increase of y in the Ba4(Nd1-y Bi y )9+1/3Ti18O54 compositions, the change of the lattice parameters has an inflection point at y=0.05. Bi was substituted into A2 sites for Ba up to y=0.05 and into A1 sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Though it was not the optimum sintering temperature, the grain size grew obviously versus substitution content with some abnormal grains for x C 0.15. All compositions had column grains which were always observed in Ba 6-3x Nd 8?2x Ti 18 O 54 ceramics [5,6,9]. Here element ratio data of the energy-dispersive X-ray analysis (EDS) of spots A and B were detected and are listed in Table 1 Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Though it was not the optimum sintering temperature, the grain size grew obviously versus substitution content with some abnormal grains for x C 0.15. All compositions had column grains which were always observed in Ba 6-3x Nd 8?2x Ti 18 O 54 ceramics [5,6,9]. Here element ratio data of the energy-dispersive X-ray analysis (EDS) of spots A and B were detected and are listed in Table 1 Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, research on both sites' simultaneous replacement was an effective way to overcome the shortcomings of those separate substitution. Also due to the fact that many other studies has reported the positive effects of single Bi substituting (0.05 B x) at Nd site on the system, goals of the investigation were to study the impact of substitution in Al-replaced Ba 3.75 Nd 9.5 Ti 18 0 54 (0.05 B x B 0.2) ceramic on microwave dielectric properties and to find a proper x value range that would conduct good dielectric properties [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, thermally stable composites could be achieved by using HDPE and PS together. Herein, Bi substituted BNT in BaO-Nd 2 O 3 -TiO 2 system was chosen as the ceramic filler because it has a high dielectric constant of 88, a low dielectric loss of  0.0005, and a f  of 0±5 ppm/℃ [12,13]; while HDPE was selected as the basic matrix. Then, a coating route with the incorporation of polystyrene (PS) was designed to improve the thermal behaviors of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten-bronze type ceramics like BaO-Nd 2 O 3 -TiO 2 (BNT) are widely used in microwave devices due to their high permittivity and low losses [4][5][6]. The substitution of Bi for Nd (BNBT ceramics) can decrease the temperature coefficient of resonant frequency and increase the permittivity of BNT based ceramics [7,8].…”
Section: Introductionmentioning
confidence: 99%